2019
DOI: 10.1021/acs.jpclett.9b00365
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics of Bismuth Triiodide in Solution Triggered by Photoinduced Ligand-to-Metal Charge Transfer

Abstract: Bismuth triiodide, BiI3, is one of the simplest bismuth halides, which have recently attracted considerable attention because of their promising properties. Here, we investigate the structural dynamics of a photoinduced reaction of BiI3 in solution phase using time-resolved X-ray liquidography (TRXL) and density functional theory (DFT) and time-dependent DFT (TDDFT) calculations. The photoreaction was initiated by excitation at 400 nm, which corresponds to the ligand-to-metal charge-transfer transition. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…A powerful method to disentangle the electronic and nuclear motions of 3d transition metal complexes during ultrafast nonadiabatic processes is time-resolved 1s-2p (Ka) and 1s-3p (Kβ) X-ray Emission Spectroscopy (XES) [10][11][12][13][14] combined with Wide Angle X-ray Scattering (WAXS) [15][16][17][18][19][20][21][22][23]. These experiments have been utilized to assign the electronic and structural motions during excited state dynamics [24][25][26] and to project the locations of conical intersections between excited state potential energy surfaces onto critical structural coordinates [27].…”
Section: Introductionmentioning
confidence: 99%
“…A powerful method to disentangle the electronic and nuclear motions of 3d transition metal complexes during ultrafast nonadiabatic processes is time-resolved 1s-2p (Ka) and 1s-3p (Kβ) X-ray Emission Spectroscopy (XES) [10][11][12][13][14] combined with Wide Angle X-ray Scattering (WAXS) [15][16][17][18][19][20][21][22][23]. These experiments have been utilized to assign the electronic and structural motions during excited state dynamics [24][25][26] and to project the locations of conical intersections between excited state potential energy surfaces onto critical structural coordinates [27].…”
Section: Introductionmentioning
confidence: 99%
“…A TRXL study at a synchrotron with 100 ps temporal resolution investigated the photochemical reaction dynamics of BiI 3 in acetonitrile solution and found that BiI 3 undergoes complex photoreactions involving two parallel reaction pathways. 34 Specifically, upon 400 nm excitation, a BiI 3 molecule (i) dissociates to yield radical fragments, and I˙, or (ii) isomerizes to form iso-BiI 2 –I. The photodynamics of BiI 3 is schematically depicted in Fig.…”
Section: Bond Cleavage and Formationmentioning
confidence: 99%
“…30 and 31)), and metal halides (HgI 2 , 32,33 HgBr 2 , 32,33 BiI 3 (ref. 34)), and photo-induced structural rearrangement of metal complexes ([Ir 2 (dimen) 4 ] 2+ (dimen = 1,8-diisocyano- p -menthane), 35 [Fe(btbip) 2 ] 2+ (btbip = 2,6-bis(3- tert -butyl-imidazol-1-ylidene)pyridine), 36 and [Pt 2 (P 2 O 5 H 2 ) 4 ] 4− 37 ). For macromolecular systems such as proteins, information about the overall structure such as size and shape can be obtained through the small-angle X-ray scattering (SAXS) region of TRXL signals, and more detailed structures such as the movement of alpha helices or beta sheets can be obtained through the signal from the wide-angle X-ray scattering (WAXS) region of TRXL signals.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, halide coordination compounds of main group metal ions with an outer shell n s 2 configuration, such as Sn 2+ , Sb 3+ , Bi 3+ , and Te 4+ , have gained substantial attention. In addition to the catalytic properties, these metal ions have found to be of use as dopants in many photophysical applications. Recently, interest has been devoted to bismuth halide-based perovskites, a low-toxicity and low-cost alternative to lead-based halide perovskites, , due to their physical and optical properties in photovoltaic technologies. Many prospective bismuth-based perovskites adopt a MX 6 octahedral structural motif, the photophysical properties of which have been of long-standing interest in Bi-doped crystals. , As of late, the photochemistry of Bi­( III )­I 6 3– ion and its parent Bi­( III )­I 3 compound has gained attention in room-temperature solutions as photoinitiated reactions that form I–I bonds.…”
Section: Introductionmentioning
confidence: 99%